Adsorption induced enzyme denaturation: the role of protein surface in adsorption induced protein denaturation on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Thudi, Lahari; Jasti, Lakshmi Swarnalatha; Swarnalatha, Y.; Fadnavis, Nitin W.; Mulani, Khudbudin Baban; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2012)
The effects of protein size on adsorption and adsorption-induced denaturation of proteins on copolymers of allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) have been studied. Different responses were observed for the amount of protein adsorbed and denatured on the polymer surface for different proteins (trypsin, alchol dehydrogenase from baker's yeast (YADH), glucose dehydrogenase (GDH) from Gluconobacter cerinus, and alkaline phosphates from calf intestinal mucosa (CIAP). Protein adsorption on the copolymer with 25% crosslink density (AGE-25) was dependent not only on the size of the protein but also on the presence of glycoside residues on the protein surface. Adsorption and denaturation of proteins follows the order YADH > trypsin > GDH >> CIAP although the molecular weights of the proteins follow the order YADH > CIAP > GDH > trypsin. The lack of correlation between amount of adsorbed protein and its molecular weight was due to the presence of glycoside residues on CIAP and GDH which protect the enzyme surface from denaturation. Enzyme stabilities in aqueous solutions of 1-cyclohexyl-2-pyrrolidinone (CHP) correlate well with the trend in denaturation by the copolymer, strongly suggesting that hydrophobic interactions play a major role in protein binding and the mechanism of protein denaturation is similar to that for water-miscible organic solvents. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1-Cyclohexyl-2-pyrrolidinone; Adsorption; Alcohol dehydrogenase; Alkaline phosphatase; allyl glycidyl ether; Denaturation; ethylene glycol dimethacrylate; Glucose dehydrogenase; Trypsin

Differential protease activity augments polyphagy in helicoverpa armigera - Chikate, Yojana R.; Tamhane, V. A.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Insect Molecular Biology, 2013)
Helicoverpa armigera (Lepidoptera: Noctuidae) and other polyphagous agricultural pests are extending their plant host range and emerging as serious agents in restraining crop productivity. Dynamic regulation, coupled with a diversity of digestive and detoxifying enzymes, play a crucial role in the adaptation of polyphagous insects. To investigate the functional intricacy of serine proteases in the development and polyphagy of H.armigera, we profiled the expression of eight trypsin-like and four chymotrypsin-like phylogenetically diverse mRNAs from different life stages of H.armigera reared on nutritionally distinct host plants. These analyses revealed diet- and stage-specific protease expression patterns. The trypsins expressed showed structural variations, which might result in differential substrate specificity and interaction with inhibitors. Protease profiles in the presence of inhibitors and their mass spectrometric analyses revealed insight into their differential activity. These findings emphasize the differential expression of serine proteases and their consequences for digestive physiology in promoting polyphagy in H.armigera.
Keywords: adaptation; chymotrypsin; Helicoverpa armigera; polyphagy; Trypsin

Comparison of polymer induced and solvent induced trypsin denaturation: the role of hydrophobicity - Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Addepally, Uma; Daniels, Siona; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Colloids and Surfaces B-Biointerfaces, 2014)
Trypsin adsorption from aqueous buffer by various copolymers of allyl glycidyl ether-ethylene glycol dimethacrylate (AGE-EGDM) copolymer with varying crosslink density increases with increasing crosslink density and the effect slowly wears off after reaching a plateau at 50% crosslink density. The copolymer with 25% crosslink density was reacted with different amines with alkyl/aryl side chains to obtain a series of copolymers with 1,2-amino alcohol functional groups and varying hydrophobicity. Trypsin binding capacity again increases with hydrophobicity of the reacting amine and a good correlation between logP(octanol) of the amine and protein binding is observed. The bound trypsin is denatured to the extent of 90% in spite of the presence of hydrophilic hydroxyl and amino groups. The behavior was comparable to that in mixtures of aqueous buffer and water-miscible organic co-solvents where the solvent concentration required to deactivate 50% of the enzyme (C-50) is dependent on logP(octanol) of the co-solvent. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Denaturation; Hydrophobicity; Polymer; Trypsin

Protein-coated polymer as a matrix for enzyme immobilization: immobilization of trypsin on bovine serum albumin-coated allyl glycidyl ether-ethylene glycol dimethacrylate copolymer - Jasti, Lakshmi Swarnalatha; Dola, Sandhya Rani; Kumaraguru, Thenkrishnan; Bajja, Sreedhar; Fadnavis, Nitin W.; Addepally, Uma; Rajdeo, Kishor; Ponrathnam, Surendra; Deokar, Sarika Babasaheb (Biotechnology Progress, 2014)
Allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymer with 25% crosslink density (AGE-25) shows excellent bovine serum albumin (BSA) adsorption (up to 16% (w/w)) at pH 8.0 and the adsorbed BSA is strongly bound. This protein-coated polymer provides a novel matrix with naturally existing functional groups such as thiol, amino, and carboxylic acid that are available for covalent immobilization of functional enzymes. Employing appropriate strategies, trypsin as a model protein was covalently bound to BSA-coated matrix both independently, and in a stepwise manner on the same matrix, with less than 5% loss of enzyme activity during immobilization. Glutaraldehyde crosslinking after immobilization provide stable enzyme preparation with activity of 510 units/g recycled up to six times without loss of enzyme activity. AFM studies reveal that the polymer surface has protein peaks and valleys rather than a uniform monolayer distribution of the protein and the immobilized enzyme preparation can best be described as polymer supported cross-linked enzyme aggregates (CLEAs). (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:317-323, 2014
Keywords: allyl glycidyl ether; Bovine serum albumin; ethylene glycol dimethacrylate; Immobilization; Trypsin

Structural insights into the unique inhibitory mechanism of Kunitz type trypsin inhibitor from Cicer arietinum L. Vol. 37 - Bendre, Ameya D.; Suresh, C. G.; Shanmugam, Dhanasekaran; Ramasamy, Sureshkumar (Journal of Biomolecular Structure & Dynamics, 2019)
Kunitz-type trypsin inhibitors bind to the active pocket of trypsin causing its inhibition. Plant Kunitz-type inhibitors are thought to be important in defense, especially against insect pests. From sequence analysis of various Kunitz-type inhibitors from plants, we identified CaTI2 from chickpea as a unique variant lacking the functionally important arginine residue corresponding to the soybean trypsin inhibitor (STI) and having a distinct and unique inhibitory loop organization. To further explore the implications of these sequence variations, we obtained the crystal structure of recombinant CaTI2 at 2.8 angstrom resolution. It is evident from the structure that the variations in the inhibitory loop facilitates non-substrate like binding of CaTI2 to trypsin, while the canonical inhibitor STI binds to trypsin in substrate like manner. Our results establish the unique mechanism of trypsin inhibition by CaTI2, which warrant further research into its substrate spectrum.
Keywords: Chickpea; crystal structure; inhibitory loop; Kunitz trypsin inhibitor; Trypsin